10.1111/j.1467-9620.2005.00583.x (CrossRef Listing of Deleted DOIs, 2000)
This article explores how rare diseases reveal the moral and epistemic foundations of healthcare systems. Based on narrative interviews with 11 Chilean patients and 10 professionals, this study shows how the absence of standardised protocols-such as clinical guidelines, treatment pathways and referral standards-exposes informal, discretionary and morally complex decision-making processes. Contrary to the ideal of evidence-based care, rare disease treatment often relies on personal networks, institutional gaps and improvisation. We frame rare diseases as epistemic objects, conditions that challenge classification systems and highlight the normative assumptions behind health decisions. Introducing the concept of decisional justice, we examine how health systems support (or fail to support) fair and accountable decision-making. Patients become epistemic activists, whereas professionals navigate fragmented institutions with little guidance. Rare diseases act as diagnostic tools that expose structural inequities and the invisibility of certain conditions. They reveal how ignorance can translate into neglect, shifting responsibility to individuals and deepening disparities. We argue that healthcare systems are not only logistical but also moral infrastructures, shaping what can be known and acted upon. Thus, health justice must also involve moral recognition and epistemic inclusion, not just resource distribution.